Implementasi Text Mining untuk Mengetahui Kata Abreviasi dalam Percakapan Media Sosial - Yunarfi, Geovaldo Reggie; Simdy, Ricky; Jackson (Journal of Digital Ecosystem for Natural Sustainability, 2021)
Social media are technology that allow sharing or exchange of information, ideas, interests, etc., via virtual communities and networks. Social media is often use for chatting either private chat or commenting on posts, and most frequently used application in Indonesia such as Facebook, WhatsApp, Instagram, Twitter, and so on. So far, peoples are typing using abbreviations as habit instead using full word and thus cause misunderstanding for others. Descriptive qualitative method was used to collect data. Text mining is a data science technique which mine data in the form of text and look for words that can represent or analyze the content of the document, and by using network of terms that can build a graph for knowing interactions between words in document. In this study, with implementing data preprocessing in text mining process is expected to reduce word or text that are not necessary, which made analyze easier to find out abbreviations within captions or comments.